Examination of Harmony Elements In Physically Disabled Families - Annisa Syakina; Siti Sa'adah; Bondan Dewabrata (Ann Publisher, 2025)
Background. The marriage of a family with a physical disability, both husband and wife or one of them with a physical disability, is not as easy as a family in a normal married condition. The foundation must be religion, because in Islam, marriage is not only a civil contract but also a matter of worship. The Quran describes the bond between husband and wife as the most sacred and strongest bond. Marriage between a man and a woman and uniting to live as husband and wife in the bond of marriage is one of the characteristics of man since he was first created. Method. The method was carried out using 10 respondents from families with physical disabilities who filled out the questionnaire, including (1) how many years they have been married, (2) how communication has occurred so far, and (3) how communication and support between married couples facilitate disability conditions. Questionnaire fill-ins were processed using SPSS. Conclusion. In realizing a harmonious family despite its limitations, it is not an excuse not to fulfill its roles and obligations as a husband and a wife. It is essential to maintain communication with your partner, accept each other, and work together effectively in carrying out daily routines. Implications. The practical implication is that married couples with disabilities can live in harmony and carry out their roles and obligations as husband and wife well, even with their limitations.